Population structure and genetic diversity of Toona sinensis revealed by whole-genome resequencing - Lei Wang; Chang Lu; Zhi-Gang Bao; Meng Li; Fusheng Wu; Yi-Zeng Lu; Bo-Qiang Tong; Mei Yu; Yong-Jun Zhao (BMC Genomic Data)
Abstract Objectives Toona sinensis, commonly known as Chinese toon, is a perennial woody plant with significant economic and ecological importance. This study employed whole-genome resequencing of 180 T. sinensis samples collected from Shandong to analyze genetic variation and diversity, ultimately identifying 18,231 high-quality SNPs after rigorous quality control and linkage disequilibrium pruning. This comprehensive genomic resource provides novel insights into the genetic architecture of T. sinensis, facilitating the elucidation of population structure and supporting future breeding programs. Data description We performed whole-genome resequencing on 180 Toona sinensis samples, generating 1170.26 Gbp of clean data with a Q30 percentage of 93.69%. The average alignment rate to the reference genome was 96.72%, with an average coverage depth of 8 × and a genome coverage of 88.71%. Following data quality control and alignment, we performed SNP calling and filtering to identify high-quality SNPs across all samples. Population structure analyses were then conducted using the identified SNPs, including principal component analysis (PCA), structure analysis, and phylogenetic tree construction. These comprehensive analyses provide a foundation for understanding the genetic diversity and evolutionary dynamics of T. sinensis.